Digital Narrative in Shelley Jackson’s Patchwork: Hypertext as a Mode of Reading and Writing - Khlifi, Roua (International Journal of Language and Literary Studies, 2025)
In Patchwork Girl, Shelley Jackson reimagines Mary Shelley’s pioneer work, Frankenstein through using digital media to reshape the narrative structure and the thematic complexity of the novel. Through using hypertext format, Jackson explores a fragmented and nonlinear storytelling approach that challenges the confines ofthe traditional narrative forms. Hypertext links invites readers to navigate the story choosing which path to take which blurs the boundaries between author, text and reader. This article will explore the role of technology in the narrative structure of Jackson’s Patchwork Girl and will analyze the interplay between content and form which highlights the reader as a co-creator of meaning.